2013
DOI: 10.1177/0047287513513169
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Employees

Abstract: High year-to-year retention of seasonal employees can be a source of competitive advantage for tourism organizations. Past studies of seasonal employee retention have examined the issue from the perspective of job satisfaction. However, many tourism jobs have similar responsibilities from organization to organization suggesting another construct might also affect employee retention. The purpose of this study was to examine retention through the lens of employee sense of community (SOC) toward the tourism organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This article also contributes to the growing body of literature on the unique challenges and issues related to mountain resort tourism, such as those relating to seasonal workers. While research by Ismert and Petrick (2004) and McCole (2013) has examined the importance of attracting and retaining quality seasonal workers from the perspective of the ski industry, this study highlights the importance of seasonal worker integration and retention from a host community perspective. These sociocultural implications, alongside the economic implications for the ski industry, are important to ensure the long-term stability of mountain resort communities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This article also contributes to the growing body of literature on the unique challenges and issues related to mountain resort tourism, such as those relating to seasonal workers. While research by Ismert and Petrick (2004) and McCole (2013) has examined the importance of attracting and retaining quality seasonal workers from the perspective of the ski industry, this study highlights the importance of seasonal worker integration and retention from a host community perspective. These sociocultural implications, alongside the economic implications for the ski industry, are important to ensure the long-term stability of mountain resort communities.…”
Section: Discussionmentioning
confidence: 97%
“…This is supported by research by Ismert and Petrick (2004) who identified that the social networks formed as a result of tourism employment provide the best indication as to whether seasonal employees return. Similarly, a more recent study by McCole (2013) has identified sense of community as being a good predictor of seasonal employee retention, particularly among experienced seasonal workers. Such socialization and the formation of social networks have also been found to provide tourism workers with opportunities to integrate into the host community (Janta et al 2011).…”
Section: Seasonal Workersmentioning
confidence: 90%
“…A sense of community among hospitality workers has replaced the traditional norm of neighborhoods, towns, churches, and other places of interactions in everyday life (McCole, 2015;Robinson, Kralj, Solnet, Goh, & Callan, 2014). When a hospitality employee feels attached to work during personal life events, the individual may decide to remain (Tews, Stafford, & Michel, 2014).…”
Section: Hospitality Employee Retentionmentioning
confidence: 99%
“…When a hospitality employee feels attached to work during personal life events, the individual may decide to remain (Tews, Stafford, & Michel, 2014). Employees may use a sense of community as a hygiene factor, and contribute to the intention to remain at an organization (McCole, 2015). Karatepe (2014) posited to help employees feel the organization is investing in the worker's career; organizations should use training, rewards, and career opportunities.…”
Section: Hospitality Employee Retentionmentioning
confidence: 99%
“…Hospitality and tourism (H&T) industry are predominantly seasonal in Turkey. The seasonal nature of the H&T industry brings with itself difficulties in business and policy formulation (Baum, 1999; McCole, 2015). Although seasonal employment is quite common and continuous in the H&T industry, the problems, expectations, needs and behaviors of seasonal employees serving in high season have been overlooked in the literature.…”
Section: Introductionmentioning
confidence: 99%